PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE QUIZ TEAM UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KOMETENSI DASAR MENGIDENTIFIKASI BENTUK PASAR DALAM KEGIATAN EKONOMI MASYARAKAT KELAS VIII-C SMP NEGERI 1 JANGKAR KABUPATEN - Raudhatul Jannah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study was conducted to enhance student’s learning activity and their learning outcome on Social Science Subject with Basic Competency Identifying market from economic activities by using cooperative learning model Quiz Team. Learning process on social science subject still implement conventional model, such as lecture. The lecture method was more focused to the teacher, while students as listeners, and teacher oftens assign students to write or memorize the material. As a result, we often hear that social science learning was bored andsaturated, even students to be passive in any learning-process, which ultimately did not reach the minimum learning mastery criteria 75. In order social science learning process becomes more meaningful, then the teacher must be able to choose model, method, and learning strategies which suitable with the materials. This study will implement cooperative learning model Quiz Team in social science subject on class VIII-C. This study was classroom action research with Kemmis and Mc Taggart model, which conducted in two cycles. This action was accompanied by research instrument, that is observation, interviews and tests. This study was conducted in class VIII-C State Junior High School 1 Jangkar as many as 25 students. These results indicate an increase in learning activity and learning outcomes in social science subject after the implementation of Quiz Team learning model. The percentage of student’s learning activity on the first cycle was 78.25%, and student’s learning outcome reached 76%, while the percentage learning activity on the second cycle was increased to 91.25% with “very active” criteria, and learning outcomes was equal to 92. Based on student’s learning activity and learning outcomes which obtained on cycle I and II, it can be concluded that the implementation of cooperative learning model Quiz Team in class VIII-C can be used as one of alternative methods that can be used to improve student’s learning activity and their learning outcomes.